COMPARATIVE ASSESSMENT OF THE EFFECTIVENESS OF CARIES PREVENTION IN CHILDREN LIVING IN THE TRANSCARPATHIAN REGION - O.V. Klytinska; V.V. Shetelya; N.V. Layoch; T.I. Zorivcthak; A.V. Stishkovskyy; L.V. Kornienko (Український стоматологічний альманах, 2023)
Prevention of dental diseases is an economically justified, promising and effective area of modern dentistry, especially for children.